Practical and stereoselective electrocatalytic 1,2-diamination of alkenes - Chen-Yan Cai (Nature Portfolio, 2019)
Methods to prepare 1,2-diamines are desirable due the importance of these compounds as drug scaffolds and organic ligands for metals. Here, the authors report an electrochemical metal-free 1,2- diamination of aryl alkenes with sulfamides to 1,2-diamines with excellent diastereoselectivity.